Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1985
DOI: 10.1093/bja/57.2.192
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Actions of Fentanyl and Buprenorphine

Abstract: Receptor binding assays were undertaken in an attempt to elucidate the opioid binding characteristics of fentanyl and buprenorphine, and to investigate some of the differences between them. Buprenorphine showed slow receptor association (30 min), but with high affinity to multiple sites from which dissociation was very slow (T 1/2 = 166 min) and incomplete (50% binding after 1 h). This contrasted with the receptor binding of fentanyl, which achieved rapid equilibrium (within 10 min) and dissociated equally rap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
115
0
3

Year Published

1994
1994
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(124 citation statements)
references
References 11 publications
6
115
0
3
Order By: Relevance
“…In addition to this, the slow binding kinetics of buprenorphine suggest that a full response may not occur for up to half an hour [6], which is consistent with clinical experience that precipitated withdrawal does not occur immediately, with a time of onset of approximately 20 minutes. This is clearly too long to wait for a response in an overdose situation.…”
Section: The Use Of Sublingual Buprenorphine-naloxone For Reversing Hsupporting
confidence: 82%
See 1 more Smart Citation
“…In addition to this, the slow binding kinetics of buprenorphine suggest that a full response may not occur for up to half an hour [6], which is consistent with clinical experience that precipitated withdrawal does not occur immediately, with a time of onset of approximately 20 minutes. This is clearly too long to wait for a response in an overdose situation.…”
Section: The Use Of Sublingual Buprenorphine-naloxone For Reversing Hsupporting
confidence: 82%
“…In Baltimore, Maryland, a recent review of the city's intoxication deaths over the past 13 years found that a very small percentage of opioid-related deaths also involved benzodiazepines [6,7]. The majority involved no other substance except cocaine.…”
Section: The Use Of Buprenorphine To Reverse Opioid Overdose Deservesmentioning
confidence: 99%
“…[4][5][6][7] These opioids produce satisfactory analgesia for 24hours postoperatively, but are frequently associated with side effects like respiratory depression, itching, nausea, vomiting and urinary retention. [8][9][10][11][12] Other adjuvants like ketamine, neostigmine has been tried but none has become established in regular clinical practice. Various studies have shown that intrathecal clonidine produces prolongation of spinal anaesthesia and reduces the need of post-operative analgesic requirement and there is now adequate evidence that clonidine given intrathecally produces antinociceptive effects without any neurotoxicity and may be useful in the treatment of somatic pain.…”
mentioning
confidence: 99%
“…This feature may lead to the persistent occupation of the opioid receptors by 030418. Several early reports have also demonstrated that 6,14-bridged oripavine compounds have very powerful binding interactions with opioid receptors and thus slow receptor kinetics, which causes a long-lasting effect [35][36][37] .…”
Section: Discussionmentioning
confidence: 99%